High-throughput assays for detection of the F1534C mutation in the voltage-gated sodium channel gene in permethrin-resistant Aedes aegypti and the distribution of this mutation throughout Thailand - Yanola J. (2014)
To develop rapid monitoring tools to detect the F1534C permethrin-resistance mutation in domain IIIS6 of the Aedes aegypti voltage-gated sodium channel gene and determine the frequency and distribution of this mutation in Thailand.